Is there a role for tedizolid in the treatment of non-tuberculous mycobacterial disease?. (30th December 2019) - Ruth, Mike Marvin; Koeken, Valerie A C M; Pennings, Lian J; Svensson, Elin M; Wertheim, Heiman F L; Hoefsloot, Wouter; van Ingen, Jakko
Abstract: Background: Pulmonary infections caused by non-tuberculous mycobacteria (NTM) are hard to treat and have low cure rates despite intensive multidrug therapy. Objectives: To assess the feasibility of tedizolid, a new oxazolidinone, for the treatment of Mycobacterium avium and Mycobacterium abscessus . Methods: We determined MICs of tedizolid for 113 isolates of NTM. Synergy with key antimycobacterial drugs was assessed using the chequerboard method and calculation of the FIC index (FICI). We performed time–kill kinetics assays of tedizolid alone and combined with amikacin for M. abscessus and with ethambutol for M. avium . Human macrophages were infected with M. abscessus and M. avium and subsequently treated with tedizolid; intracellular and extracellular cfu were quantified over time. Results: NTM isolates generally had a lower MIC of tedizolid than of linezolid. FICIs were lowest between tedizolid and amikacin for M. abscessus (FICI = 0.75) and between tedizolid and ethambutol for M. avium (FICI = 0.72). Clarithromycin and tedizolid showed initial synergy, which was abrogated by erm (41)-induced macrolide resistance (FICI = 0.53). Tedizolid had a weak bacteriostatic effect on M. abscessus and combination with amikacin slightly prolonged its effect. Tedizolid had concentration-dependent activity against M. avium and its efficacy was enhanced by ethambutol. Both combinations had a concentration-dependent synergistic effect. Tedizolid could inhibit the intracellular bacterial population of both M. avium and M. abscessus . Conclusions: Tedizolid should be further investigated in pharmacodynamic studies and clinical trials for M. avium complex pulmonary disease . It is less active against M. abscessus, but still promising.